Experience of industrial tribunals/dismissal, 1978 - Dickens, Linda (UK Data Service, 1983)
The aim of this study was to explore the experiences and perceptions of dismissed workers and their ex-employers who had been involved in an application for unfair dismissal to an industrial tribunal, whether or not the case was eventually heard by a tribunal.